2010
DOI: 10.1152/ajprenal.00595.2009
|View full text |Cite
|
Sign up to set email alerts
|

Detrusor overactivity is associated with downregulation of large-conductance calcium- and voltage-activated potassium channel protein

Abstract: Large-conductance voltage- and calcium-activated potassium (BK) channels have been shown to play a role in detrusor overactivity (DO). The goal of this study was to determine whether bladder outlet obstruction-induced DO is associated with downregulation of BK channels and whether BK channels affect myosin light chain 20 (MLC(20)) phosphorylation in detrusor smooth muscle (DSM). Partial bladder outlet obstruction (PBOO) was surgically induced in male New Zealand White rabbits. The rabbit PBOO model shows decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 28 publications
6
64
1
Order By: Relevance
“…Interestingly, BKα knockout mice (20) display a functionally incontinent phenotype, presumably due to detrusor overactivity. Furthermore, a number of studies (21,22) have suggested that the expression of BK channels is reduced in patients suffering from neurogenic detrusor overactivity. These results suggest that BK channel activators could represent a novel therapeutic approach for treating overactive bladder.…”
Section: +mentioning
confidence: 99%
“…Interestingly, BKα knockout mice (20) display a functionally incontinent phenotype, presumably due to detrusor overactivity. Furthermore, a number of studies (21,22) have suggested that the expression of BK channels is reduced in patients suffering from neurogenic detrusor overactivity. These results suggest that BK channel activators could represent a novel therapeutic approach for treating overactive bladder.…”
Section: +mentioning
confidence: 99%
“…Antimuscarinic drugs, which are currently the primary pharmacologic therapy for OAB, have adverse side effects and limited effectiveness (1). Since BK channels have been identified to play a prominent role in the regulation of DSM excitability and contractility, they may be a valid pharmacological target for the treatment of bladder disorders such as OAB (5,15,20,23,31,34,35,38). Development of drugs that can enhance BK channel activity have been proposed and investigated particularly as a treatment option for urinary bladder dysfunction (3,4,17,37).…”
mentioning
confidence: 99%
“…Bladder outlet obstruction is considered one of the key factors in BPH-induced lower urinary tract symptoms (LUTS) in aged men (41,42), and it is associated with remodeling and hypertrophy of the BSM that eventually leads to contractile dysfunction (41,42). PBOO-induced smooth muscle remodeling and hypertrophy are associated with altered expression of contractile, signaling, and regulatory proteins (16,20,29,35,(43)(44)(45)(46). Similar to the murine PBOO model, we observed increased expression of NF-B c-Rel and p50 in BSM from obstructed bladders compared with their expression in bladders from healthy controls (Fig.…”
Section: Nf-b P50 and C-rel Are Required For Cpi-17 Gene Expression Imentioning
confidence: 99%